Mathematical modelling and exergo-environmental analysis of drying potato samples in a waste heat-based convective dryer - Mahadi Hasan Masud (Elsevier, 2021)
Understanding the drying kinetics within a food dryer is an important step towards its improvement. This study investigates the drying kinetics of potato slices in a recently proposed waste-heat based convective dryer. Statistical analyses are conducted for ten dissimilar mathematical models to choose the best fit model for the experimental data at various drying temperatures (70 °C, 60 °C, and 50 °C). Results show that the Midilli et al. model is the best fit model to describe the drying kinetics of potato in the proposed dryer as it offers root mean square error (RMSE) of 0.0022, a coefficient of determination (R2) of 0.99, reduced chi-square (χ2) of 9.2 ×10−7. Results also demonstrate that the activation energy is 47.19 kJ⁄mol and the effective moisture diffusivity of dried potato sample is 4.22 ×10−10 to 11.67 × 10−10 m2/s at a drying air temperature of 50–70 °C. Moreover, if the proposed waste-heat based convective dryer is used instead of an electric convective dryer at 60 °C, it can reduce the external energy requirement by 29.98 MJ/kg. Exergo-environmental analysis of the proposed dryer shows that the CO2 emission and CO2 mitigation values for 20-year life cycle periods are 184.46 kg/year and 17.24 tons, respectively. Therefore, successful industrial application of the proposed drying system might be a striding stone towards the advancement of energy-efficient sustainable food drying systems.